2006
DOI: 10.1196/annals.1372.005
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Tribulus terrestris in Diabetes

Abstract: Tribulus terrestris L (TT) is used in the Arabic folk medicine to treat various diseases. The aim of this article was to investigate the protective effects of TT in diabetes mellitus (DM). Diabetes is known to increase reactive oxygen species (ROS) level that subsequently contributes to the pathogenesis of diabetes. Rats were divided into six groups and treated with either saline, glibenclamide (Glib), or TT for 30 days. Rats in group 1 were given saline after the onset of streptozotocin (STZ)-induced diabetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 18 publications
3
60
0
7
Order By: Relevance
“…Due to the heterogeneous nature of this disease, there is an urgent need to find effective and appropriate therapies. Recently, researchers have shown that herbal remedies can help improve diabetic complications (26). There are several well-known plants with hypoglycemic effects, such as Teucrium polium, Smallanthus sonchifolius (yacon), Psacalium peltatum, and Cucurbita ficifolia (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the heterogeneous nature of this disease, there is an urgent need to find effective and appropriate therapies. Recently, researchers have shown that herbal remedies can help improve diabetic complications (26). There are several well-known plants with hypoglycemic effects, such as Teucrium polium, Smallanthus sonchifolius (yacon), Psacalium peltatum, and Cucurbita ficifolia (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…Saponin from T. terrestris reported to possess hypoglycemic properties and produced protective effect in streptozotocin-induced diabetic rats by inhibiting oxidative stress [23]. Some of the main active compounds of T. terrestris identified and purified include: steroidal furostanol and spirostanol saponins -protodioscin, terrestrinins A and B, gitogenin, hecogenin, diosgenin and others [22].…”
Section: Discussionmentioning
confidence: 99%
“…Hence this protective effect of T. terrestris can be used for the treatment of angina pectoris and cardiac diseases and the level of ROS (reactive oxygen specie) can be inhibited. [17] Li M et al, 2001 extracted saponins from T. terrestris as they possess hypoglycemic properties and examined on mice. On treatment with T. terrestris though reduced the level of serum glucose, triglyceride and cholesterol but increased the serum superoxide dismutase level that contributed to the pathogenesis of diabetes.…”
Section:  Anti-fungal Effectmentioning
confidence: 99%